Reference values for T and B lymphocyte subpopulations in Turkish children and adults - ÖZEN, AHMET OĞUZHAN; BORAN, PERRAN; BARIŞ, SAFA (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2021)
Background/aim: Established reference values are critical for the interpretation of immunologic assessments. In particular, the proportion and absolute counts of T-and B-cell subpopulations are subject to change with age and ethnicity. We aimed to establish age-specific reference values for lymphocyte subsets using updated immunophenotyping panels. Materials and methods: We studied a total of 297 healthy Turkish subjects aged 0 to 50 years, stratified into major age brackets in a cluster factor of 10 per age-group. The predetermined age intervals contained randomly allocated participants enrolled over a period of 6 months, who were homogenously distributed by sex. We analyzed a complete blood count test and simultaneously with detailed immunophenotyping enumerated the percent and absolute cell counts of lymphocyte subsets. Results: The percentage and absolute counts of lymphocyte subsets show a marked surge across the age-span. T helper, T cytotoxic, and the natural killer cell numbers were increasing from birth until 6 months, followed by a gradual decrease thereafter. B cell numbers were rising until 2 years, followed by a gradual decrease for the upcoming years, accompanied by a steady expansion of unclass-switched-and class-switched-B cells. Discussion: We provide updated extensive reference intervals for lymphocyte subpopulations in Turkish people.
Keywords: Immunophenotyping; lymphocyte subsets; reference values; lymphocyte percentage; absolute count; HEALTHY-CHILDREN; SUBSETS; AGE; BIRTH